1990
DOI: 10.1161/01.cir.82.4.1305
|View full text |Cite
|
Sign up to set email alerts
|

Altered myocardial perfusion in patients with angina pectoris or silent ischemia during exercise as assessed by quantitative thallium-201 single-photon emission computed tomography.

Abstract: The extent of abnormally perfused myocardium was compared in patients with and without chest pain during treadmill exercise from a large, relatively low-risk consecutive patient population (n=356) referred for quantitative thallium-201 single-photon emission computed tomography (SPECT). All patients had concurrent coronary angiography. Patients were excluded if they had prior coronary angioplasty or bypass surgery. Tomographic images were assessed visually and from computer-generated polar maps. Chest pain dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…Some investigators have reported a greater extent and severity of ischaemia in symptomatic patients than in those with silent myocardial ischaemia, [11][12][13][14][15][16] whereas other studies reported no difference in the amount of ischaemic myocardium between patients with and patients without symptomatic myocardial ischaemia during exercise or pharmacological stress testing. [4][5][6][7][8][9][10] In the present study there are no significant differences between dysfunctional segments at rest and the number of ischaemic segments at peak in patients with and without symptomatic myocardial ischaemia. Moreover, the extent of ischaemia during DSE was an independent predictor of cardiac death and myocardial infarction, and the number of diseased vessels was related to an increased rate of cardiac events, particularly in patients with symptomatic ischaemia.…”
Section: Comparison With Previous Studiescontrasting
confidence: 57%
“…Some investigators have reported a greater extent and severity of ischaemia in symptomatic patients than in those with silent myocardial ischaemia, [11][12][13][14][15][16] whereas other studies reported no difference in the amount of ischaemic myocardium between patients with and patients without symptomatic myocardial ischaemia during exercise or pharmacological stress testing. [4][5][6][7][8][9][10] In the present study there are no significant differences between dysfunctional segments at rest and the number of ischaemic segments at peak in patients with and without symptomatic myocardial ischaemia. Moreover, the extent of ischaemia during DSE was an independent predictor of cardiac death and myocardial infarction, and the number of diseased vessels was related to an increased rate of cardiac events, particularly in patients with symptomatic ischaemia.…”
Section: Comparison With Previous Studiescontrasting
confidence: 57%
“…Discordant results have been published on the functional significance of silent versus symptomatic ischaemia during exercise stress testing [15][16][17][18][19][20]. Re-versible exercise-thallium defects were reported to be more extensive and severe in patients with compared to those without angina in the studies of Klein et al [15] and Travin et al [16], while others failed to demonstrate such a difference [17][18][19][20]. Klein et al [15] concluded that the induction of pain is associated with substantially more functional abnormalities when patients with a broad spectrum of coronary artery disease are evaluated.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Additionally, in patients with myocardial infarction and stress-induced ST-segment elevation, concomitant ST-segment depression may represent reciprocal changes without true ischaemia. Hecht et al [20] and Mahmarian et al [19] reported that in patients with coronary artery disease, positive and negative exercise electrocardiographic findings were associated with a similar amount of ischaemia on exercise thallium scintigraphy. Conversely, Hecht et al [25] concluded that exercise-induced STsegment depression is the single most significant variable in relation to the amount of ischaemic myocardium assessed by exercise echocardiography.…”
Section: St-segment Depression and The Amount Of Ischaemiamentioning
confidence: 99%
“…However, no other similar results have been reported. Because physiologically a perfusion defect must precede an electrocardiographic change [7] and many studies have indicated that exercise thallium imaging is more accurate than conventional exercise electrocardiogram [8,9], we hypothesized that thallium single-photon emission computed tomography (SPECT) is a better imaging modality than the ST/HR slope in the detection of coronary artery disease. The current study was undertaken to (1) test our hypothesis and (2) evaluate the effect of exercise level on the sensitivity and specificity of the ST/HR slope, conventional electrocardiographic criteria and thallium SPECT.…”
Section: Introductionmentioning
confidence: 99%